NATIONAL SPECIFICITY OF UZBEK-RUSSIAN TRANSLATIONS - Khasanova L. A. (Journals Park Publishing, 2025)
The article summarizes the results of the study of literary translation, assessing the quality of national specifics rendering and the individual style of the writer. The material for the study is the translation of the novel "Almazny Pojas" (Diamond Belt) by Pirimkul Kadyrov from Uzbek into Russian by Yu. Suvortsev, as well as the interlinear translation performed by the author himself. The explanatory potential of the hermeneutic approach to analyzing the source and translated texts is demonstrated. The article characterizes cases of successful translation solutions in recreating the national worldview reflected in the source text, which are revealed in the reproduction of wordplay, proverbs, etc.
Keywords: Translation, national specificity, Uzbek-Russian literature, translation strategy.